2011
DOI: 10.2119/molmed.2010.00183
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation of GJB2 Variants in Nonsyndromic Hearing Loss

Abstract: Histone deacetylase (HDAC) inhibitors are currently used clinically as anticancer drugs. Recent data have demonstrated that some of these drugs have potent antiinflammatory or immunomodulatory effects at noncytotoxic doses. The immunomodulatory effects have shown potential for therapeutic benefit after allogeneic bone marrow transplantation in several experimental models of graft versus host disease (GVHD). These effects, at least in part, result from the ability of HDAC inhibitors (HDACi) to suppress the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 88 publications
2
20
0
1
Order By: Relevance
“…KID S17F (+*) [ 13 , 40 , 123 , 136 ] (−) (−) S, SNHL. KID TM1 V27I [ 140 ] Normal Normal NS, HL and Normal I33T [ 141 ] (−) n.d. NS, Severe to Profound M34T [ 36 , 115 , 142 146 ] (−) (−) NS, Mild to Moderate; S, Profound. PPK V37I, A40G [ 113 , 143 , 147 – 149 ] (−) (−) NS, Mild-Moderate, Severe A40V [ 124 , 136 , 150 , 151 ] Normal (+) S, Profound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KID S17F (+*) [ 13 , 40 , 123 , 136 ] (−) (−) S, SNHL. KID TM1 V27I [ 140 ] Normal Normal NS, HL and Normal I33T [ 141 ] (−) n.d. NS, Severe to Profound M34T [ 36 , 115 , 142 146 ] (−) (−) NS, Mild to Moderate; S, Profound. PPK V37I, A40G [ 113 , 143 , 147 – 149 ] (−) (−) NS, Mild-Moderate, Severe A40V [ 124 , 136 , 150 , 151 ] Normal (+) S, Profound.…”
Section: Introductionmentioning
confidence: 99%
“…Profound T86R, A88S, L90P [ 132 , 143 , 144 , 147 , 160 , 180 ] (−) (−) NS, Profound, Moderate to Profound, Mild to Moderate A88V [ 136 , 168 , 181 ] n.d. (+) S, Severe to Profound. KID ICL E114G, R127H [ 115 , 140 , 144 , 173 , 178 , 182 , 183 ] (−) (−) NS, Severe to Profound, Profound DelE120 [ 141 , 143 , 147 ] (−) n.d. NS, Severe to Profound TM3 R143Q, R153I [ 133 , 152 , 153 , 183 , 184 ] (−) n.d. NS, Profound R143W [ 133 , 144 , 178 , 185 , 186 ] (−) (−) NS, Profound ECL2 F161S, P173R, D179N, R165W, W172R, R184P, R184Q [ 132 , 141 , 143 , 147 , 152 , 153 , 187 190 ] (−) n.d. NS, H...…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 , 9 , 10 Additional variants V27I and E114G were also evaluated and found to cause hearing loss in certain conditions, including VG homozygotes or a compound heterozygote with VG. 11 Interestingly, defects in hemichannel activities were less severe when both loci were mutated, indicating that V27I compensated for the deleterious effect of E114G. Another interesting case showed that R75Q, a dominant GJB2 mutation, was silenced by the cis recessive mutation c.35delG.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the other missense variant, p.V291L, in the serine protease domain ( Figure 2 d), was predicted to be non-pathogenic with poor conservation among species, from humans to zebrafish ( Figure 2 c). Additionally, another study from Korea reported that p.V291L was likely to be a rare polymorphism ( Table 2 ) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%